Suggested clinical approach for the diagnosis and management of 'statin intolerance' with an emphasis on muscle‐related side‐effects. Issue 9 (10th September 2019) - Sivashanmugarajah, Anosh; Fulcher, Jordan; Sullivan, David; Elam, Marshall; Jenkins, Alicia; Keech, Anthony
Abstract: Hyperlipidaemia is a major risk factor for cardiovascular morbidity and mortality. 3‐hydroxy‐3‐methylglutaryl coenzyme‐A reductase inhibitors ('statins') are first‐line therapies for hyperlipidaemia. For each 1.0 mmoL/L reduction in low‐density lipoprotein (LDL)‐cholesterol, statins reduce the risk of major vascular events by 21% and all‐cause mortality by 9%. Owing to their clinical effectiveness and excellent safety profile, many Australians are prescribed statins. There has been widespread reporting of possible side‐effects, particularly muscle pains. Conversely, statin cessation relating to possible side‐effects exposes patients to increased risk of vascular events and death. Although there is clinical consensus for diagnosing rare side‐effects (e.g. myopathy or rhabdomyolysis), confirming that statins cause other less common side‐effects (e.g. memory impairment) is difficult as strong randomised trial evidence related to statins and non‐muscle‐related side‐effects is lacking. A stepwise approach to possible statin intolerance, consistent definitions and a simple flowchart may improve diagnosis and management. An increasing array of potential treatments is emerging, including intermittent statin dosing, new LDL‐lowering drugs, LDL apheresis and supplements. Optimal statin use and management of statin intolerance should improve cardiovascular care and clinical outcomes.